Whole-genome analysis of the SHORT-ROOT developmental pathway in Arabidopsis - Levesque, Mitchell P.; Lohmann, Jan U. (PLoS biology, 2006)
Meta-analysis to combine the results of several microarray experiments reveals a new function for the transcription factor SHORT-ROOT in the development of vascular tissue.